ANALISIS PENGAKUAN, PENGUKURAN, DAN PENGUNGKAPAN PENDAPATAN MENURUT SAK ETAP PADA PT. METTA KARUNA JAYA - Manegeng, Peggy Natasia; Sondakh, Jullie J.; Pusung, Rudy J. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
The goal with every company is trying to gain the advantage or profit which is the maximum. Income the main of its trade comes from the sale of the goods so that the account of sales is used instead of the account of income. Problems main for income is a defining moment was this recognation of income. On the principles of recognation of income, generally income is recognized at the time be realized or can be realized and produced. Not just a matter of recognation, but also concerning the measurement and disclosure income. When entering the income in the report, the financial not correspond with the standard that applies, then there would be a mistake information for the internal and external company. This research aims at knowing of correspondence recognation, measurement, and disclosure income according to Standard Accounting Financial Entities Without Accountability Public on PT. Metta Karuna Jaya. The method of research that use is descriptive kualitatif with the use of data primary and data secondary. The result of the research show that the revenue stream PT. Metta Karuna Jaya comes from the sale of goods, the company’s recognizes revenue in accordance with the SAK ETAP based on accrual basis, measuring income in accordance with the fair value that can be accepted, and disclose revenue in accordance SAK ETAP in the report profit loss company.Keywords : revenue, recognation, measurement, disclosure, SAK ETAP